In-ear hearing test probe devices and methods and systems using same - Givens, Gregg; Yao, Jianchu (My University, 2017)
A medical hearing testing method includes: inserting an in-ear test probe that is coupled to a hearing test adapter into an ear of a patient at a patient site; receiving device identification data at a web portal operating on a first electronic device over an electronic network between the first electronic device and the hearing test adapter, wherein the device identification data is uniquely identifies the hearing test adapter; receiving a control operation associated with a test session from the first user at the web portal; and responsive to receiving the control operation, transmitting an operational command from the web portal to the hearing test adapter over the electronic network, wherein the operational command controls an operation of the test probe.
Inventors: Givens; Gregg D. (Greenville, NC), Yao; Jianchu (Winterville, NC) Full text available: http://patft.uspto.gov/netacgi/nph-Parser?Sect1=PTO1&Sect2=HITOFF&d=PALL&p=1&u=%2Fnetahtml%2FPTO%2Fsrchnum.htm&r=1&f=G&l=50&s1=10368785.PN.&OS=PN/10368785&RS=PN/10368785
Keywords: Test; Ear; Internet